2017
DOI: 10.1007/s40708-016-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of brain morphology estimates

Abstract: Metrics of brain morphology are increasingly being used to examine inter-individual differences, making it important to evaluate the reliability of these structural measures. Here we used two open-access datasets to assess the intersession reliability of three cortical measures (thickness, gyrification, and fractal dimensionality) and two subcortical measures (volume and fractal dimensionality). Reliability was generally good, particularly with the gyrification and fractal dimensionality measures. One dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
112
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 111 publications
11
112
3
Order By: Relevance
“…With regard to our empirical results, deviation analyses suggested a high overall test-retest stability of the fractal dimension estimates (approximately 95 %) across both the MASSIVE and the MSC data sets. This is in accordance with a recent reliability study of brain morphology estimates in two openaccess data sets by Madan and Kensinger (Madan and Kensinger, 2017) who found that regional fractal dimensionality as computed by both dilation and box-counting methods was generally very high and comparable to the reliability of gyrication indices, while it was in fact superior to volumetric measures such as cortical thickness. Similarly, Goñi and colleagues analyzed the fractal properties of the pial surface, the gray matter / white matter boundary and the cortical ribbon and white matter volumes in MRI data from dierent imaging centers and found a high within-subject reproducibility with regionspecic patterns of individual variability (Goñi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to our empirical results, deviation analyses suggested a high overall test-retest stability of the fractal dimension estimates (approximately 95 %) across both the MASSIVE and the MSC data sets. This is in accordance with a recent reliability study of brain morphology estimates in two openaccess data sets by Madan and Kensinger (Madan and Kensinger, 2017) who found that regional fractal dimensionality as computed by both dilation and box-counting methods was generally very high and comparable to the reliability of gyrication indices, while it was in fact superior to volumetric measures such as cortical thickness. Similarly, Goñi and colleagues analyzed the fractal properties of the pial surface, the gray matter / white matter boundary and the cortical ribbon and white matter volumes in MRI data from dierent imaging centers and found a high within-subject reproducibility with regionspecic patterns of individual variability (Goñi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Since cortical thickness has been reported as highly reliable 55 , the negative correlation between gray matter thickness and sulcal width shown in our study ( Figure S22 ) supports the hypothesis that inter-subject variability, and by consequence sulcal labeling performance, affects the reliability of sulcal shape descriptors in addition to segmentation performance.…”
Section: Discussionsupporting
confidence: 86%
“…A trivial difference between scan-rescan PVS maps was observed, which are most likely due to 1) segmentation imperfection and image intensity differences of scan-rescan signal (e.g. due to subject motion) (Madan and Kensinger, 2017;Reuter et al, 2015), 2) normal physiological changes of PVS in the same subject, such as potential effects of time-of-day and hydration on morphometric estimates of PVS (Dickson et al, 2005;Kempton et al, 2009;Trefler et al, 2016).…”
Section: Discussionmentioning
confidence: 99%